Improving the quality of life of the people in Dukoh Kidul, Candisari Village, Magelang Regency - Heni Setyowati Esti Rahayu; Dwi Rahayu Sulistyorini; Nining Setiyo Apriyani; Whanovita Prima Listiany; Thoriq Kurniawati (Community Empowerment, 2023)
Adequacy of nutrition and food is an indicator of the success of a nation's development. One of the nutritional problems that is still quite high in Indonesia is stunting in toddlers with rates that are still relatively high. Magelang Regency is one of the contributors to the high number of stunting cases in Central Java province, including Candisari Village, Windusari District. It is hoped that this Integrated Community Service Activity (PPMT) will have an impact on the Candisari village community in reducing malnutrition rates. The series of activities carried out included training for posyandu cadres in handling stunting, education for couples in early marriage, education for mothers with toddlers aged 0-5 years about nutritional problems in overcoming stunting and making complementary foods, and gymnastics. Through these activities, the knowledge of cadres increases so that services at the posyandu get better. In addition, teenagers are increasingly aware of the dangers of early marriage and children are motivated to exercise and like to eat fish as a source of protein to support children's growth.